Platform Pragmatics - Edoardo Biscossi (A Peer-Reviewed Journal About, 2024)
This article proposes platform pragmatics as a framework for understanding collective behaviour and forms of labour within platform ecosystems. It contributes to the field of platform criticism by problematising a certain view of users as passive victims of surveillance and algorithmic governmentality. The main argument is developed by thinking through the production of content and forms by users, and their circulation through computational logic and aective contagion. Through some illustrative cases and analyses of cultural habits, the article addresses the political and aesthetic configuration of these forms of production — not only of content/forms, but also of culture and subjectivity. This is explored by thinking through three themes: the subsumption of creativity and opportunism in platform economies; the mobilisation of speculative temporalities not only in computation but also across user practices; and the generalisation of self-reflexivity as a feminised cultural behaviour and aesthetic mode. Finally, I propose to understand platform pragmatics as a mode of subaltern power, that might be alien to traditional political reason, but precisely because of this needs to be grappled with through inventive cultural and social criticism.